2007
DOI: 10.1590/s0100-67622007000200016
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura da vegetação arbórea de um remanescente ecotonal urbano floresta-savana no Parque do Sabiá, em Uberlândia, MG

Abstract: Neste estudo, avaliou-se a estrutura do componente arbóreo de manchas de vegetação correspondentes à Floresta Estacional Semidecidual e dois cerradões, inseridas em um remanescente urbano composto também por uma mancha de mata de brejo. O levantamento compreendeu 1,32 ha, onde todos os indivíduos com perímetro à altura do peito > 5 cm foram amostrados. Registraram-se 141 espécies, distribuídas em 46 famílias botânicas, com diversidade de Shannon de 3,99. Fabaceae apresentou a maior riqueza de espécies no le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
(10 reference statements)
4
12
1
9
Order By: Relevance
“…The Pielou evenness determined in this present study (0.76) corroborated the values reported elsewhere (0.73-0.91;SALIS et al, 2006;NAKAJIMA, 2007). The evenness score for the cerradão indicated moderate diversity and surpassed 76% of the maximum possible value (Hmax) because of the dominance of some species in the area (MAGURRAN, 2004).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The Pielou evenness determined in this present study (0.76) corroborated the values reported elsewhere (0.73-0.91;SALIS et al, 2006;NAKAJIMA, 2007). The evenness score for the cerradão indicated moderate diversity and surpassed 76% of the maximum possible value (Hmax) because of the dominance of some species in the area (MAGURRAN, 2004).…”
Section: Resultssupporting
confidence: 90%
“…Its density was also very high. Nevertheless, in the forest-savannah areas of São Paulo, Mato Grosso do Sul, Minas Gerais, Goias, and Distrito Federal, this species does not have the highest IVI (COSTA; ARAÚJO, 2001;NAKAJIMA, 2007;MARIMON JUNIOR;HARIDASAN, 2005). On the other hand, the floristic inventory performed by Solórzano et al (2012) indicated that, in the cerradão area of Tocantins, this species was among the most important species and commonly occurred in the region's cerradão.…”
Section: Resultsmentioning
confidence: 96%
“…This value was within the range of floristic diversity found in other cerradão areas by Solórzano et al (2012) (2.92 to 3.54 nats individuals -1 ). The Pielou equality was 0.76, which was within the values previously found in cerradão areas (0.73 and 0.91) (GUILHERME; NAKAJIMA, 2007;SALIS et al, 2006). The equality value found in this cerradão indicates that a reasonable diversity, with values higher than 76% of the maximum possible (Hmax), resulting in the possible dominance of certain species in the area (MAGURRAN, 2004), which was confirmed in this study.…”
Section: Nij Nsupporting
confidence: 90%
“…Atualmente, os cerradões são encontrados em pequenos fragmentos isolados ou em contato com outras fitofisionomias do Cerrado, como cerrado stricto sensu, mata de galeria e mata seca ou floresta estacional (Guilherme & Nakajima, 2007). Dos estudos já realizados em áreas de cerradão, a grande maioria trata apenas da caracterização de sua flora (composição, riqueza e diversidade) e da estrutura de sua vegetação.…”
Section: Introductionunclassified